Diachronically Changing False Friends in Latvian (Interpreters’ Outlook) - Ķiršakmene, Evelīna (Vertimo studijos, 2025)
False friends are pairs of words in two or more languages that resemble each other in form (spelling, pronunciation, or both) but differ in meaning, often leading to misunderstandings or mistranslations. Unfortunately, like any other linguistic units, they are subject to change. The growing influence of English can be observed in many languages of the world, including Latvian. This has lead to the semantic broadening of some words previously considered strict and well-known false friends. The aim of this paper is to determine the actual use of five diachronically changing false friends in Latvian. A contrastive dictionary analysis is employed, along with excerpts from the press and a corpus. A survey of Latvian interpreters was also conducted to explore their experiences. The results provide evidence that some false friends are now predominantly used in Latvian with their English meaning, thus having partially become “true friends”, and highlight the need to assess the current usage of other false friends.
Keywords: false friends; interference; semantic broadening; diachronic changes; interpreting